A method for preparing ablation-resistant high-temperature resistant ceramic material

By mixing hafnium carbide, hafnium nitride with modified chopped carbon fiber, composite reinforcement and other materials, and using cold isostatic pressing and discharge plasma sintering processes, ablation-resistant and high-temperature-resistant ceramic materials are prepared, which solves the problem The existing ceramic materials have insufficient ablation resistance at high temperatures, so ceramic materials have high-efficiency thermal shock resistance and ablation resistance.

CN119059819BActive Publication Date: 2025-01-21SHANDONG RES & DESIGN ACADEMY OF IND CERAMICS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411578007.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-01-21
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

The existing ceramic materials have insufficient ablation resistance at high temperatures, and their performance is significantly reduced after rapid heating and cooling, making it difficult to meet the thermal protection needs of spacecraft.

Method used

Hafnium carbide, hafnium nitride is mixed with modified chopped carbon fibers, composite reinforcements, carbon powder, carbon nitride and other materials. After cold isostatic pressing and discharge plasma sintering processes, ablation-resistant and high-temperature resistant materials are prepared. Ceramic material.

Benefits of technology

It significantly improves the thermal shock resistance, ablation resistance and fracture toughness of ceramic materials, and avoids the reduction of ablation resistance after rapid heating and cooling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention provides a method for preparing an ablation-resistant and high-temperature resistant ceramic material, which belongs to the field of ceramic materials. The method for preparing an ablation-resistant and high-temperature resistant ceramic material consists of the following steps: preparing a mixture, cold isostatic pressing, and discharge plasma sintering. The method for preparing an ablation-resistant and high-temperature resistant ceramic material of the present invention can effectively improve the bonding performance of the reinforcing phase component with hafnium carbide and hafnium nitride ceramics, the overall stability of the ceramic material is good, and the thermal shock resistance of the ceramic material is effectively improved, and the reduction of the ablation resistance of the ceramic material after rapid heating and cooling is effectively avoided; and the high temperature resistance, ablation resistance and fracture toughness of the ceramic material are simultaneously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ceramic materials, and in particular to a method for preparing an ablation-resistant and high-temperature-resistant ceramic material. Background Art

[0002] With the advancement of aerospace technology, the research on spacecraft has been heating up in recent years. From space shuttles to reusable carriers to hypersonic vehicles, when flying through the atmosphere, due to the friction between the surface of the vehicle and the surrounding air and the compression of the air in front, the spacecraft will be subjected to severe aerodynamic heating, high temperature and structural thermal stress, which has a significant impact on the safety of the spacecraft. Therefore, the outer surface material of the spacecraft plays an extremely important role in its safety and flight stability. At present, there are more and more studies on thermal protection materials for the outer surface of spacecraft.

[0003] When a spacecraft flies at high speed in the Earth's atmosphere, the friction of the atmospheric airflow on its surface will cause severe aerodynamic heating on the thermal protection materials. With the increase of the Mach number of the spacecraft, the thermal protection technology of the spacecraft has become more and more important, especially for the thermal protection materials used in the nose cone cap, wing leading edge, tail cone and other parts of the spacecraft. The demand for thermal protection materials that can withstand high temperatures, resist ablation, and have good mechanical properties and thermal shock resistance is becoming more and more urgent.

[0004] In the prior art, commonly used thermal protection materials mainly include refractory metals, C / C materials, ceramic materials, etc. Among them, refractory metals and C / C materials have bottlenecks in high-temperature oxidation resistance and ablation resistance, and it is difficult to meet the thermal protection requirements of aerospace vehicles. Ceramic materials have the advantages of high melting point, oxidation resistance, and good physical and chemical stability. In recent years, they have been widely used as thermal protection materials for aerospace vehicles.

[0005] At present, although there are documents that disclose the use of hafnium carbide and hafnium nitride to prepare high temperature resistant and ablation resistant ceramic materials, the ceramic materials prepared therefrom have poor thermal shock resistance, and the ablation resistance of the ceramic materials decreases significantly after rapid heating and cooling. At the same time, the ceramic materials prepared using hafnium carbide and hafnium nitride have poor toughness and are prone to brittle fracture when subjected to impact or vibration loads.

[0006] Furthermore, in order to improve the above defects, in the process of using reinforcing phase components for ceramic materials prepared from hafnium carbide and hafnium nitride, the ceramic materials prepared from hafnium carbide and hafnium nitride have poor compatibility with the reinforcing phase components and poor bonding performance, resulting in poor overall stability of the final ceramic material, and the above defects cannot be effectively improved. Summary of the invention

[0007] In order to solve the technical problems existing in the prior art, the present invention provides a method for preparing an ablation-resistant and high-temperature resistant ceramic material, which can effectively improve the bonding performance of the reinforcing phase component with hafnium carbide and hafnium nitride ceramics, and the overall stability of the ceramic material is good. It can also effectively improve the thermal shock resistance of the ceramic material, and effectively avoid the reduction of the ablation resistance of the ceramic material after rapid heating and cooling; and simultaneously improve the high temperature resistance, ablation resistance and fracture toughness of the ceramic material.

[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0009] A method for preparing an ablation-resistant and high-temperature-resistant ceramic material comprises the following steps: preparing a mixed material, cold isostatic pressing, and spark plasma sintering.

[0010] The method for preparing the mixture is as follows: putting hafnium carbide powder, hafnium nitride powder, composite reinforcing agent, carbon powder, carbon nitride powder, triethyl phosphate and ethanol solution into a ball mill, controlling the ball-to-material ratio to 7-7.5:1, the ball milling speed to 200-250rpm, and ball milling for 3-4h to obtain a ball-milled product; then putting the ball-milled product and modified short-cut carbon fiber into a high-speed mixer, controlling the mixing speed to 2000-2300rpm, and after uniform mixing, transferring to a vacuum drying oven, drying at 80-85°C to constant weight in a vacuum environment of 0.08-0.09MPa, and sieving to obtain a mixture.

[0011] In the prepared mixture, the weight ratio of hafnium carbide powder, hafnium nitride powder, composite reinforcing agent, carbon powder, carbon nitride powder, triethyl phosphate, ethanol solution and modified short-cut carbon fiber is 28-30:19-21:7-7.5:2.3-2.5:2.3-2.5:0.4-0.5:30-33:5.5-5.8.

[0012] The modified chopped carbon fiber is prepared by the following steps: pretreatment and composite treatment.

[0013] The pretreatment method comprises the following steps: putting short-cut carbon fibers with a diameter of 0.4-0.5 μm and a length of 12-15 mm into a pretreatment liquid of 5-6 times its weight, performing ultrasonic dispersion for 10-20 minutes, heating the liquid to 55-60° C. with stirring at a heating rate of 0.8-1° C. / min, maintaining the temperature with stirring for 10-12 hours, filtering and separating to obtain a solid; then washing the solid with deionized water to neutrality, transferring the solid to a vacuum drying oven, and drying the solid at 90-95° C. to constant weight in a vacuum environment of 0.05-0.07 MPa to obtain the pretreated fiber.

[0014] In the pretreatment, the pretreatment liquid is prepared by adding tannic acid into a Tris-HCl buffer solution with a pH of 8.5 and dispersing the tannic acid uniformly; the weight ratio of the tannic acid to the Tris-HCl buffer solution is 4.3-4.7:100.

[0015] The composite treatment method is as follows: placing the pretreated fiber in a deposition furnace, completely replacing the air in the deposition furnace with nitrogen, evacuating the deposition furnace to a vacuum degree of 10-12 Pa, heating the furnace to 900-930° C. under nitrogen protection, keeping the temperature for 50-60 minutes, introducing hydrogen, and controlling the flow rate of hydrogen to 480-500 mL / min; while continuously introducing hydrogen, introducing a first gas and a second gas at the same time, and controlling the flow rate of the first gas to 50-55 mL / min and the flow rate of the second gas to 30-35 mL / min, respectively, and maintaining the pressure in the deposition furnace to 0.35-0.40 KPa; after chemical vapor deposition for 1.5-2 hours, stopping the introduction of hydrogen, the first gas and the second gas, and cooling the furnace naturally to room temperature to obtain modified short-cut carbon fibers.

[0016] In the composite treatment, the first gas is a mixed gas of cyclopentadienane volatile gas and hydrogen; in the first gas, the mass ratio of cyclopentadienane volatile gas to hydrogen is 1:2.3-2.4;

[0017] The second gas is a mixed gas of liquid polycarbosilane volatile gas and hydrogen; in the second gas, the mass ratio of liquid polycarbosilane volatile gas to hydrogen is 1:1.35-1.4.

[0018] The preparation method of the composite reinforcing agent comprises the following steps: adding zirconium boride, hafnium boride, silicon carbide and anhydrous ethanol into a plasma discharge assisted ball mill at a weight ratio of 3-3.5:1-1.2:2.3-2.5:0.06-0.07, controlling the ball-to-material ratio to 27-28:1, the ball milling speed to 400-500rpm, the plasma discharge current to 1.2-1.3A, and performing plasma discharge assisted ball milling for 2-3h in an argon atmosphere environment to obtain the composite reinforcing agent.

[0019] The cold isostatic pressing method comprises placing the mixed material in a sealed mold, placing the mixed material in a cold isostatic pressing machine, controlling the cold isostatic pressing pressure to be 280-320 MPa, performing the cold isostatic pressing for 20-30 minutes, demolding, and obtaining a formed body.

[0020] The method for spark plasma sintering comprises the following steps: placing a formed green body in a graphite mold of the same size, and then transferring the formed green body into a spark plasma sintering furnace, controlling the sintering pressure in the spark plasma sintering furnace to be 48-50MPa, heating the green body to 1000-1050°C at a heating rate of 85-95°C / min, and sintering the green body at a heat preservation rate of 85-95°C / min for 8-10min; heating the green body to 1900-2000°C at a heating rate of 85-95°C / min, and sintering the green body at a heat preservation rate of 12-15min for spark plasma sintering; cooling the green body to room temperature at a cooling rate of 55-65°C / min, and demolding the green body to obtain an ablation-resistant and high-temperature resistant ceramic material.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] (1) The method for preparing the ablation-resistant and high-temperature resistant ceramic material of the present invention comprises mixing hafnium carbide, hafnium nitride with modified chopped carbon fibers, a composite reinforcing agent, carbon powder and carbon nitride to obtain a mixture; the mixture is subjected to cold isostatic pressing and then to discharge plasma sintering to obtain the ablation-resistant and high-temperature resistant ceramic material; wherein, in the pretreatment step of preparing the modified chopped carbon fibers, the chopped carbon fibers are pre-modified with a tannic acid solution, and the surface modification effect of the tannic acid in the pretreatment solution on the chopped carbon fibers is used to increase the roughness of the outer surface of the carbon fibers, increase the specific surface area, and improve the chopped carbon fibers. The wettability of the fiber is improved, and active groups are introduced at the same time to promote the chemical bonding between the chopped carbon fiber and the SiBCN coating in the subsequent composite treatment step, improve the interface bonding performance of the chopped carbon fiber and the SiBCN coating, and improve the overall stability of the modified chopped carbon fiber finally obtained; then in the composite treatment step, a chemical vapor deposition method is adopted, and a first gas containing cycloborane and a second gas containing polycarbosilane are used to form a SiBCN coating with good structural stability, high temperature resistance and ablation resistance on the outer surface of the chopped carbon fiber. The modified chopped carbon fiber finally obtained has good thermal conductivity and good thermal conductivity when combined with hafnium carbide, During the molding and sintering process after the hafnium nitride and other raw materials are combined, the compatibility of the modified short-cut carbon fiber with hafnium carbide and hafnium nitride is further improved, the bonding performance between the raw materials is improved, and the energy is dispersed through the bridging, pulling out and fracture mechanism of the modified short-cut carbon fiber, thereby simultaneously improving the high temperature resistance, ablation resistance and fracture toughness of the ceramic material; further, in the preparation of the composite reinforcing agent, zirconium boride, hafnium boride and silicon carbide raw materials are selected, and plasma discharge assisted ball milling is carried out in combination, and the etching effect of plasma discharge on the surface of the material changes the microscopic morphology of the material surface, improves the surface roughness of the material, and at the same time introduces Active groups are introduced to improve the bonding performance between the composite reinforcement component and hafnium carbide and hafnium nitride ceramics, and the thermal shock resistance and ablation resistance stability of the ceramic material are improved through the dispersion bonding and strengthening effect of the composite reinforcement component; the aforementioned technical means cooperate with each other and work synergistically to effectively improve the bonding performance between the reinforcement phase component and hafnium carbide and hafnium nitride ceramics, the overall stability of the ceramic material is good, and the thermal shock resistance of the ceramic material is effectively improved, and the reduction of the ablation resistance of the ceramic material after rapid heating and cooling is effectively avoided; and the high temperature resistance, ablation resistance and fracture toughness of the ceramic material are simultaneously improved.

[0023] (2) The method for preparing the ablation-resistant and high-temperature resistant ceramic material of the present invention has a density of 99.4-99.5%, a Rockwell hardness of 96-97HRA, a heat-resistant temperature of 2800-2820°C, a room temperature flexural strength of 430-434MPa, and a room temperature fracture toughness of 6.9-7.0MPa·m 1 / 2; After 2500℃ oxyacetylene ablation for 420s, the thickness of the ablation layer is 519-525μm, the mass ablation rate is 0.218-0.222mg / s, and the line ablation rate is 0.55-0.57μm / s.

[0024] (3) The method for preparing the ablation-resistant high-temperature ceramic material of the present invention comprises heating the material to 2000°C at a heating rate of 40°C / min in an air atmosphere, and then keeping the temperature for 8 hours; then cooling the material to room temperature at a cooling rate of 25°C / min; after 20 consecutive times, the room temperature flexural strength is 408-415MPa, and the room temperature fracture toughness is 6.7-6.9MPa·m 1 / 2 ; After 2500℃ oxyacetylene ablation for 420s, the thickness of the ablation layer was 541-549μm, the mass ablation rate was 0.230-0.236mg / s, the line ablation rate was 0.58-0.59μm / s, and no cracking or deformation occurred.

[0025] (4) The method for preparing the ablation-resistant and high-temperature resistant ceramic material of the present invention has an easy-to-control process, high safety, and is conducive to industrial-scale production. DETAILED DESCRIPTION

[0026] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.

[0027] Example 1

[0028] A method for preparing an ablation-resistant and high-temperature resistant ceramic material, specifically comprising:

[0029] 1. Prepare the mixture

[0030] Hafnium carbide powder, hafnium nitride powder, composite reinforcing agent, carbon powder, carbon nitride powder, triethyl phosphate and ethanol solution (volume concentration 60%) are put into a ball mill, the ball-to-material ratio is controlled to be 7:1, the ball milling speed is 200 rpm, and the ball milling is performed for 3 hours to obtain a ball-milled product; then the ball-milled product and modified short-cut carbon fiber are put into a high-speed mixer, the mixing speed is controlled to be 2000 rpm, and after uniform mixing, the mixture is transferred into a vacuum drying oven, dried at 80°C to constant weight in a vacuum environment of 0.08 MPa, and sieved to obtain a mixture.

[0031] Among them, the weight ratio of hafnium carbide powder, hafnium nitride powder, composite reinforcing agent, carbon powder, carbon nitride powder, triethyl phosphate, ethanol solution, and modified chopped carbon fiber is 28:19:7:2.3:2.3:0.4:30:5.5.

[0032] The modified chopped carbon fiber is prepared by the following steps:

[0033] 1) Preprocessing

[0034] Short-cut carbon fibers with a diameter of 0.4 μm and a length of 13 mm were put into 5 times the weight of a pretreatment liquid, and after ultrasonic dispersion for 10 minutes, the temperature was raised to 55°C with stirring at a heating rate of 0.8°C / min. After keeping warm and stirring for 10 hours, the solid was separated by filtration. The solid was then washed with deionized water until neutral, transferred to a vacuum drying oven, and dried at 90°C to constant weight in a vacuum environment of 0.05 MPa to obtain pretreated fibers.

[0035] The pretreatment solution is prepared by adding tannic acid into a Tris-HCl buffer solution with a pH of 8.5 and dispersing the tannic acid uniformly; the weight ratio of tannic acid to Tris-HCl buffer solution is 4.3:100.

[0036] 2) Composite treatment

[0037] The pretreated fiber was placed in a deposition furnace, and after the air in the deposition furnace was completely replaced by nitrogen, the vacuum degree in the deposition furnace was evacuated to 10Pa. Under nitrogen protection, the temperature was raised to 900°C, and after keeping warm for 50 minutes, hydrogen was introduced, and the flow rate of hydrogen was controlled to 480mL / min; under the condition of continuous introduction of hydrogen, the first gas and the second gas were introduced at the same time, and the flow rate of the first gas was controlled to 50mL / min, and the flow rate of the second gas was controlled to 30mL / min, respectively, and the pressure in the deposition furnace was maintained at 0.35KPa; after chemical vapor deposition for 1.5 hours, the introduction of hydrogen, the first gas and the second gas was stopped, and the carbon fiber was naturally cooled to room temperature to obtain modified short-cut carbon fiber.

[0038] The first gas is a mixed gas of cyclopentadienane volatile gas and hydrogen; in the first gas, the mass ratio of cyclopentadienane volatile gas to hydrogen is 1:2.3.

[0039] The second gas is a mixed gas of liquid polycarbosilane volatile gas and hydrogen; in the second gas, the mass ratio of the liquid polycarbosilane volatile gas to the hydrogen is 1:1.35.

[0040] The preparation method of the composite reinforcing agent is as follows: zirconium boride, hafnium boride, silicon carbide and anhydrous ethanol are put into a plasma discharge assisted ball mill at a weight ratio of 3:1:2.3:0.06, the ball-to-material ratio is controlled to be 27:1, the ball milling speed is 400 rpm, the plasma discharge current is 1.2 A, and the plasma discharge assisted ball milling is performed for 2 hours in an argon atmosphere environment to obtain the composite reinforcing agent.

[0041] 2. Cold isostatic pressing

[0042] The mixed material is placed in a sealed mold and then placed in a cold isostatic pressing machine. The cold isostatic pressing pressure is controlled to be 280 MPa. After cold isostatic pressing for 20 minutes, the mold is removed to obtain a molded body.

[0043] 3. Spark plasma sintering

[0044] The formed body was placed in a graphite mold of the same size, and then transferred into a spark plasma sintering furnace. The sintering pressure in the spark plasma sintering furnace was controlled to be 48 MPa. The temperature was increased to 1000°C at a heating rate of 85°C / min, and the temperature was kept for sintering for 8 minutes; the temperature was increased to 1900°C at a heating rate of 85°C / min, and the temperature was kept for spark plasma sintering for 12 minutes; the temperature was cooled to room temperature at a cooling rate of 55°C / min, and the mold was demolded to obtain an ablation-resistant and high-temperature resistant ceramic material.

[0045] Example 2

[0046] A method for preparing an ablation-resistant and high-temperature resistant ceramic material, specifically comprising:

[0047] 1. Prepare the mixture

[0048] Hafnium carbide powder, hafnium nitride powder, composite reinforcing agent, carbon powder, carbon nitride powder, triethyl phosphate and ethanol solution (volume concentration 62%) are put into a ball mill, the ball-to-material ratio is controlled to be 7.2:1, the ball milling speed is 220 rpm, and the ball milling is performed for 3.5 hours to obtain a ball-milled product; then the ball-milled product and modified short-cut carbon fiber are put into a high-speed mixer, the mixing speed is controlled to be 2100 rpm, and after being evenly mixed, the mixture is transferred into a vacuum drying oven, dried at 82°C to constant weight in a vacuum environment of 0.085 MPa, and sieved to obtain a mixture.

[0049] Among them, the weight ratio of hafnium carbide powder, hafnium nitride powder, composite reinforcing agent, carbon powder, carbon nitride powder, triethyl phosphate, ethanol solution, and modified chopped carbon fiber is 29:20:7.3:2.4:2.4:0.45:31:5.7.

[0050] The modified chopped carbon fiber is prepared by the following steps:

[0051] 1) Preprocessing

[0052] Short-cut carbon fibers with a diameter of 0.4 μm and a length of 13 mm were put into 5.5 times the weight of the pretreatment liquid, and after ultrasonic dispersion for 15 minutes, the temperature was raised to 58°C with stirring at a heating rate of 0.9°C / min, and after keeping the temperature and stirring for 11 hours, the solid was separated by filtration; the solid was then washed with deionized water to neutrality, transferred to a vacuum drying oven, and dried at 92°C to constant weight in a vacuum environment of 0.06 MPa to obtain the pretreated fiber.

[0053] The pretreatment solution is prepared by adding tannic acid into a Tris-HCl buffer solution with a pH of 8.5 and dispersing the tannic acid uniformly; the weight ratio of tannic acid to Tris-HCl buffer solution is 4.5:100.

[0054] 2) Composite treatment

[0055] The pretreated fiber was placed in a deposition furnace, and after the air in the deposition furnace was completely replaced by nitrogen, the vacuum degree in the deposition furnace was evacuated to 11 Pa. Under nitrogen protection, the temperature was raised to 920°C, and after keeping warm for 55 minutes, hydrogen was introduced, and the flow rate of hydrogen was controlled to 490 mL / min; under the condition of continuous introduction of hydrogen, the first gas and the second gas were introduced at the same time, and the flow rate of the first gas was controlled to 52 mL / min, and the flow rate of the second gas was controlled to 33 mL / min, respectively, and the pressure in the deposition furnace was maintained at 0.38 KPa; after chemical vapor deposition for 1.8 hours, the introduction of hydrogen, the first gas and the second gas was stopped, and the carbon fiber was naturally cooled to room temperature to obtain modified short-cut carbon fiber.

[0056] The first gas is a mixed gas of cyclopentadienane volatile gas and hydrogen; in the first gas, the mass ratio of cyclopentadienane volatile gas to hydrogen is 1:2.35.

[0057] The second gas is a mixed gas of liquid polycarbosilane volatile gas and hydrogen; in the second gas, the mass ratio of the liquid polycarbosilane volatile gas to the hydrogen is 1:1.38.

[0058] The preparation method of the composite reinforcing agent is as follows: zirconium boride, hafnium boride, silicon carbide and anhydrous ethanol are put into a plasma discharge assisted ball mill at a weight ratio of 3.3:1.1:2.4:0.065, the ball-to-material ratio is controlled to be 27.5:1, the ball milling speed is 450rpm, the plasma discharge current is 1.25A, and the plasma discharge assisted ball milling is performed for 2.75h ​​in an argon atmosphere environment to obtain the composite reinforcing agent.

[0059] 2. Cold isostatic pressing

[0060] The mixed material is placed in a mold and sealed, and then placed in a cold isostatic pressing machine. The cold isostatic pressing pressure is controlled to be 310 MPa. After cold isostatic pressing for 25 minutes, the mold is removed to obtain a molded body.

[0061] 3. Spark plasma sintering

[0062] The formed body was placed in a graphite mold of the same size, and then transferred into a spark plasma sintering furnace. The sintering pressure in the spark plasma sintering furnace was controlled to be 49 MPa. The temperature was increased to 1030°C at a heating rate of 90°C / min, and the mixture was kept warm for 9 minutes. The temperature was increased to 1950°C at a heating rate of 90°C / min, and the mixture was kept warm for 14 minutes of spark plasma sintering. The mixture was cooled to room temperature at a cooling rate of 60°C / min, and demolded to obtain an ablation-resistant and high-temperature resistant ceramic material.

[0063] Example 3

[0064] A method for preparing an ablation-resistant and high-temperature resistant ceramic material, specifically comprising:

[0065] 1. Prepare the mixture

[0066] Hafnium carbide powder, hafnium nitride powder, composite reinforcing agent, carbon powder, carbon nitride powder, triethyl phosphate and ethanol solution (volume concentration 65%) are put into a ball mill, the ball-to-material ratio is controlled to be 7.5:1, the ball milling speed is 250rpm, and the ball milling is performed for 4 hours to obtain a ball-milled product; then the ball-milled product and modified short-cut carbon fiber are put into a high-speed mixer, the mixing speed is controlled to be 2300rpm, and after being evenly mixed, the mixture is transferred into a vacuum drying oven, dried at 85°C to constant weight in a vacuum environment of 0.09MPa, and sieved to obtain a mixture.

[0067] Among them, the weight ratio of hafnium carbide powder, hafnium nitride powder, composite reinforcing agent, carbon powder, carbon nitride powder, triethyl phosphate, ethanol solution, and modified chopped carbon fiber is 30:21:7.5:2.5:2.5:0.5:33:5.8.

[0068] The modified chopped carbon fiber is prepared by the following steps:

[0069] 1) Preprocessing

[0070] Short-cut carbon fibers with a diameter of 0.4 μm and a length of 13 mm were put into 6 times the weight of a pretreatment liquid. After ultrasonic dispersion for 20 minutes, the temperature was raised to 60°C with stirring at a heating rate of 1°C / min. After keeping warm and stirring for 12 hours, the solid was separated by filtration. The solid was then washed with deionized water until neutral, transferred to a vacuum drying oven, and dried at 95°C to constant weight in a vacuum environment of 0.07 MPa to obtain pretreated fibers.

[0071] The pretreatment solution is prepared by adding tannic acid into a Tris-HCl buffer solution with a pH of 8.5 and dispersing the tannic acid uniformly; the weight ratio of tannic acid to Tris-HCl buffer solution is 4.7:100.

[0072] 2) Composite treatment

[0073] The pretreated fiber was placed in a deposition furnace, and after the air in the deposition furnace was completely replaced by nitrogen, the vacuum degree in the deposition furnace was evacuated to 12Pa. Under nitrogen protection, the temperature was raised to 930°C, and after keeping warm for 60 minutes, hydrogen was introduced, and the flow rate of hydrogen was controlled to 500mL / min; under the condition of continuous introduction of hydrogen, the first gas and the second gas were introduced at the same time, and the flow rate of the first gas was controlled to 55mL / min, and the flow rate of the second gas was controlled to 35mL / min, respectively, and the pressure in the deposition furnace was maintained at 0.40KPa; after chemical vapor deposition for 2 hours, the introduction of hydrogen, the first gas and the second gas was stopped, and the carbon fiber was naturally cooled to room temperature to obtain modified short-cut carbon fiber.

[0074] The first gas is a mixed gas of cyclopentadienane volatile gas and hydrogen; in the first gas, the mass ratio of cyclopentadienane volatile gas to hydrogen is 1:2.4.

[0075] The second gas is a mixed gas of liquid polycarbosilane volatile gas and hydrogen; in the second gas, the mass ratio of the liquid polycarbosilane volatile gas to the hydrogen is 1:1.4.

[0076] The preparation method of the composite reinforcing agent is as follows: zirconium boride, hafnium boride, silicon carbide and anhydrous ethanol are put into a plasma discharge assisted ball mill at a weight ratio of 3.5:1.2:2.5:0.07, the ball-to-material ratio is controlled to be 28:1, the ball milling speed is 500 rpm, the plasma discharge current is 1.3 A, and the plasma discharge assisted ball milling is performed for 3 hours in an argon atmosphere environment to obtain the composite reinforcing agent.

[0077] 2. Cold isostatic pressing

[0078] The mixed material is placed in a mold and sealed, and then placed in a cold isostatic pressing machine. The cold isostatic pressing pressure is controlled to be 320 MPa. After cold isostatic pressing for 30 minutes, the mold is removed to obtain a molded body.

[0079] 3. Spark plasma sintering

[0080] The formed body was placed in a graphite mold of the same size, and then transferred into a spark plasma sintering furnace. The sintering pressure in the spark plasma sintering furnace was controlled to be 50 MPa. The temperature was increased to 1050°C at a heating rate of 95°C / min, and the temperature was kept for 10 minutes. The temperature was increased to 2000°C at a heating rate of 95°C / min, and the temperature was kept for 15 minutes of spark plasma sintering. The temperature was cooled to room temperature at a cooling rate of 65°C / min, and the mold was demolded to obtain an ablation-resistant and high-temperature resistant ceramic material.

[0081] Comparative Example 1

[0082] The technical solution of Example 2 is adopted, but the differences are as follows: 1) in the preparation of modified chopped carbon fibers, the pretreatment step is omitted; 2) in the preparation of the composite reinforcing agent is omitted, and zirconium boride, hafnium boride and silicon carbide are uniformly mixed in a weight ratio of 3.2:1.1:2.4 and then used instead of the composite reinforcing agent in the step of preparing the mixture.

[0083] Comparative Example 2

[0084] The technical solution of Example 2 is adopted, but the differences are as follows: 1) in the preparation of modified chopped carbon fibers, the composite treatment step is omitted, and the pretreated fibers obtained in the pretreatment step are used as modified chopped carbon fibers in the step of preparing a mixture; 2) in the preparation of the composite reinforcing agent, the addition of zirconium boride and hafnium boride is omitted.

[0085] The density, Rockwell hardness, heat resistance temperature (oxyacetylene temperature), room temperature flexural strength, room temperature fracture toughness of the ceramic materials obtained in Examples 1-3 and Comparative Examples 1-2, as well as the thickness of the ablation layer, mass ablation rate, and line ablation rate after 2500°C oxyacetylene ablation for 420s are shown in the following table:

[0086]

[0087] Furthermore, the ceramic materials obtained in Examples 1-3 and Comparative Examples 1-2 were placed in a calcining furnace, heated to 2000°C at a heating rate of 40°C / min in an air atmosphere, and kept warm for 8 hours; cooled to room temperature at a cooling rate of 25°C / min; the aforementioned rapid heating and cooling process was a thermal shock cycle, and after 20 consecutive cycles, the room temperature bending strength and room temperature fracture toughness of each ceramic material were measured; as well as the thickness of the ablation layer, mass ablation rate, and line ablation rate after 2500°C oxyacetylene ablation for 420s, and whether the ceramic material had cracking or deformation occurred. The specific results are shown in the following table:

[0088]

[0089] It can be seen that the preparation method of the anti-ablation and high-temperature resistant ceramic material of the present invention comprises the following steps: mixing hafnium carbide, hafnium nitride with modified chopped carbon fibers, a composite reinforcing agent, carbon powder and carbon nitride to obtain a mixture; the mixture is subjected to cold isostatic pressing and then to discharge plasma sintering to obtain the anti-ablation and high-temperature resistant ceramic material; wherein, in the pretreatment step of preparing the modified chopped carbon fibers, the chopped carbon fibers are pre-modified with a tannic acid solution, and the surface modification effect of the tannic acid in the pretreatment solution on the chopped carbon fibers is used to increase the roughness of the outer surface of the carbon fibers, increase the specific surface area, and improve the properties of the chopped carbon fibers. The wettability of carbon fiber is improved, and active groups are introduced at the same time to promote the chemical bonding between the chopped carbon fiber and the SiBCN coating in the subsequent composite treatment step, improve the interface bonding performance between the chopped carbon fiber and the SiBCN coating, and improve the overall stability of the modified chopped carbon fiber finally obtained; then in the composite treatment step, a chemical vapor deposition method is adopted, and a first gas containing cycloborane and a second gas containing polycarbosilane are used to form a SiBCN coating with good structural stability, high temperature resistance and ablation resistance on the outer surface of the chopped carbon fiber. The modified chopped carbon fiber finally obtained is In the molding and sintering process after the combination of raw materials such as hafnium carbide and hafnium nitride, the compatibility of the modified chopped carbon fiber with hafnium carbide and hafnium nitride is further improved, the bonding performance between the raw materials is improved, and the energy is dispersed through the bridging, pulling out and fracture mechanism of the modified chopped carbon fiber, thereby simultaneously improving the high temperature resistance, ablation resistance and fracture toughness of the ceramic material; further, in the preparation of the composite reinforcing agent, zirconium boride, hafnium boride and silicon carbide raw materials are selected, and plasma discharge assisted ball milling is carried out in combination, and the etching effect of plasma discharge on the surface of the material changes the microscopic morphology of the material surface, improves the surface roughness of the material, and at the same time Active groups are introduced to improve the bonding performance between the composite reinforcement component and hafnium carbide and hafnium nitride ceramics, and the thermal shock resistance and ablation resistance stability of the ceramic material are improved through the dispersion bonding and strengthening effect of the composite reinforcement component; the aforementioned technical means cooperate with each other and work synergistically to effectively improve the bonding performance between the reinforcement phase component and hafnium carbide and hafnium nitride ceramics, the overall stability of the ceramic material is good, and the thermal shock resistance of the ceramic material is effectively improved, and the reduction of the ablation resistance of the ceramic material after rapid heating and cooling is effectively avoided; and the high temperature resistance, ablation resistance and fracture toughness of the ceramic material are simultaneously improved.

[0090] Unless otherwise specified, all percentages used in the present invention are by mass.

[0091] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing an ablation-resistant and high-temperature resistant ceramic material, characterized in that: The method comprises the following steps: preparing a mixed material, cold isostatic pressing, and spark plasma sintering; The method for preparing the mixture comprises: uniformly ball-milling hafnium carbide powder, hafnium nitride powder, composite reinforcing agent, carbon powder, carbon nitride powder, triethyl phosphate and ethanol solution to obtain a ball-milled product; uniformly mixing the ball-milled product with modified short chopped carbon fiber, and drying to obtain a mixture; In the prepared mixture, the weight ratio of hafnium carbide powder, hafnium nitride powder, composite reinforcing agent, carbon powder, carbon nitride powder, triethyl phosphate, ethanol solution, and modified short carbon fiber is 28-30:19-21:7-7.5:2.3-2.5:2.3-2.5:0.4-0.5:30-33:5.5-5.8; The modified chopped carbon fiber is prepared by the following steps: pretreatment and composite treatment; The pretreatment method comprises: putting the chopped carbon fibers into a pretreatment liquid, dispersing them uniformly, heating them to 55-60° C., stirring them at the temperature, and separating and obtaining solids; washing and drying the solids to obtain pretreated fibers; The pretreatment solution is a Tris-HCl buffer solution containing tannic acid; The composite treatment method comprises placing the pretreated fiber in a deposition furnace, heating it to 900-930° C. under nitrogen protection, keeping the temperature for 50-60 minutes, and then introducing the first gas and the second gas at the same time under the condition of continuously introducing hydrogen, performing chemical vapor deposition, stopping the introduction of hydrogen, the first gas and the second gas, and naturally cooling to room temperature to obtain modified chopped carbon fiber; the first gas is a mixed gas of cyclopentadiene volatile gas and hydrogen; The second gas is a mixed gas of liquid polycarbosilane volatile gas and hydrogen; The preparation method of the composite reinforcing agent comprises the following steps: zirconium boride, hafnium boride and silicon carbide are subjected to plasma discharge assisted ball milling to obtain the composite reinforcing agent; In the preparation of the composite reinforcing agent, the weight ratio of zirconium boride, hafnium boride and silicon carbide is 3-3.5:1-1.2:2.3-2.5; After the mixed material is formed by cold isostatic pressing, spark plasma sintering is performed; The method for spark plasma sintering comprises the following steps: placing a formed green body obtained by cold isostatic pressing in a graphite mold, and then transferring the formed green body into a spark plasma sintering furnace, controlling the sintering pressure in the spark plasma sintering furnace to be 48-50 MPa, heating the green body to 1000-1050° C., and sintering the green body at the temperature for 8-10 minutes; further heating the green body to 1900-2000° C., and sintering the green body at the temperature for 12-15 minutes; cooling the green body to room temperature, and demolding the green body to obtain an ablation-resistant and high-temperature resistant ceramic material.

2. The method for preparing the ablation-resistant and high-temperature-resistant ceramic material according to claim 1, characterized in that: In the pretreatment, the diameter of the chopped carbon fibers is 0.4-0.5 μm and the length is 12-15 mm; The weight ratio of chopped carbon fiber to pretreatment liquid is 1:5-6; Keep stirring at 55-60℃ for 10-12h; The weight ratio of tannic acid to Tris-HCl buffer in the pretreatment solution is 4.3-4.7:

100.

3. The method for preparing the ablation-resistant and high-temperature-resistant ceramic material according to claim 1, characterized in that: In the composite treatment, the flow rate of hydrogen is controlled to be 480-500 mL / min, the flow rate of the first gas is controlled to be 50-55 mL / min, the flow rate of the second gas is controlled to be 30-35 mL / min, and the pressure in the deposition furnace is maintained at 0.35-0.40 kPa.

4. The method for preparing the ablation-resistant and high-temperature-resistant ceramic material according to claim 1, characterized in that: In the composite treatment, the chemical vapor deposition time is 1.5-2h; The mass ratio of the volatile gas of borazine to the hydrogen in the first gas is 1:2.3-2.4; The mass ratio of the liquid polycarbosilane volatile gas to the hydrogen in the second gas is 1:1.35-1.

4.

5. The method for preparing the ablation-resistant and high-temperature-resistant ceramic material according to claim 1, characterized in that: In the preparation of the composite reinforcing agent, the plasma discharge assisted ball milling is carried out in an argon atmosphere environment, the ball-to-material ratio is controlled to be 27-28:1, the ball milling speed is 400-500rpm, and the plasma discharge current is 1.2-1.3A; The time of plasma discharge assisted ball milling is 2-3h.

6. The method for preparing the ablation-resistant and high-temperature-resistant ceramic material according to claim 1, characterized in that: The cold isostatic pressing method comprises placing the mixed material in a sealed mold, placing the mixed material in a cold isostatic pressing machine, controlling the cold isostatic pressing pressure to be 280-320 MPa, performing cold isostatic pressing, demolding, and obtaining a formed body.

7. The method for preparing the ablation-resistant and high-temperature-resistant ceramic material according to claim 1, characterized in that: In the spark plasma sintering, the heating rate to 1000-1050°C is 85-95°C / min; The heating rate to 1900-2000°C is 85-95°C / min; The cooling rate is 55-65°C / min.

Citation Information

Patent Citations

  • Method for secondary modification of chopped carbon fibers by using polyethyleneimine

    CN107190513A

  • Long-time ablation-resistant ultrahigh-melting-point nitrogen-containing carbide ultrahigh-temperature ceramic and application thereof

    CN110845238A